Human CYP3A4-mediated toxification of the pyrrolizidine alkaloid lasiocarpine. (August 2019) - Ebmeyer, Johanna; Braeuning, Albert; Glatt, Hansruedi; These, Anja; Hessel-Pras, Stefanie; Lampen, Alfonso
Abstract: Pyrrolizidine alkaloids (PA) are widely distributed phytotoxins contaminating food and feed. Hepatic enzymes are considered to bioactivate PA. Previous studies showed differences in the metabolism rate in liver homogenates of different species. Thus, uncertainty remains with respect to the relevance of human metabolism. Our study aimed to analyze whether the PA representative lasiocarpine is toxified by human cytochrome P450 (CYP) enzymes. We compared the metabolic elimination of lasiocarpine in the presence of rat and human S9 fractions and liver microsomes. Experiments with the potent CYP3A/Cyp3a inhibitor ketoconazole and supersomes containing individual human and rat CYPs revealed that enzymes of the CYP3A/Cyp3a family of both species are of major relevance for lasiocarpine metabolism. To assess if metabolism by human CYP3A4 results in a toxification of lasiocarpine we performed experiments with V79 cells. γH2AX and micronucleus formation were analyzed as endpoints for genotoxicity. No effects were observed in the wildtype cells, which lack CYP activity. By contrast, a V79 clone engineered for expression of human CYP3A4 showed concentration-dependent γH2AX and micronucleus formation. Concluding, our results showed the CYP3A4-dependent formation of genotoxic metabolites of lasiocarpine. The results confirm previous data indicating the need to include metabolism of PA for human risk assessment. Graphical abstract: Image 1 Highlights: Turnover rates of lasiocarpine by different liver fractions of different species correlate with their total CYP content. Ketoconazole inhibits metabolism of lasiocarpine by rat and human liver fractions. Ketoconazole reduces cytotoxic effects of lasiocarpine in V79-hCYP3A4 cells. Lasiocarpine induces CYP3A4-dependent H2AX phosphorylation and micronuclei.